2016
DOI: 10.1680/jgein.15.00035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geogrid encasement on lateral and vertical deformations of stone columns in model tests

Abstract: Geosynthetic encasement of individual stone columns can provide additional confinement to the columns thus increasing their load capacities and reducing lateral and vertical deformations. Most of past studies have been focused on the load capacities and settlements (i.e. vertical deformations) of the encased stone columns. However, the load transfer mechanism and the lateral bulging deformation pattern of the encased stone columns are not thoroughly understood. In the present study, four series of laboratory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Although small-scale laboratory research has provided valuable information on the behavior of the granular columns, in order to avoid the scaling issues, researchers [20,21] have opted for large-scale tests to study the behavior of granular columns at large scale. In the large-scale studies, the stress concentration ratio of for granular columns have been reported at a wide range between 3 and 20.…”
Section: State Of the Art -Static Load Considerationsmentioning
confidence: 99%
“…Although small-scale laboratory research has provided valuable information on the behavior of the granular columns, in order to avoid the scaling issues, researchers [20,21] have opted for large-scale tests to study the behavior of granular columns at large scale. In the large-scale studies, the stress concentration ratio of for granular columns have been reported at a wide range between 3 and 20.…”
Section: State Of the Art -Static Load Considerationsmentioning
confidence: 99%
“…Malarvizhi and Ilamparuthi [17] conducted small-scale tests to investigate the improved performance of GESC and found that the ultimate bearing capacity of GESC treated beds is three times that of the untreated beds. Gu et al [18] also found that the ultimate load capacity of the soft soil was greatly increased by GESC, and the effective length of the encasement was three to four times of the diameter of stone columns. Orekanti and Dommaraju [8] conducted strain-restricted compression tests on GESC, and the results showed that GESC with lateral reinforcement of end-bearing type and floating type showed a substantial increase in load-carrying capacity relative to clay by 2.44 and 2.01 times, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Four series of laboratory model tests were performed in a large-scale testing tank to investigate the effect of geogrid encasement on the lateral and vertical deformations of stone columns installed in a clay bed. In addition, the stress-strain characteristics of the encasement were measured and analysed by Gu et al [8,9]. To provide the theoretical basis for the design and construction of an embankment with an encased stone column composite foundation, two groups of indoor model tests for the embankment with encased stone column composite foundation with different stiffnesses of the encasement were carried out in accordance with the influence of the stiffness of the encasement on the deformation and stability of the composite foundation with the encased stone column by Chen et al [10].…”
Section: Introductionmentioning
confidence: 99%